ANTI-FRAUD STRATEGY MODEL AT PT. BANK SUMUT - Lubis, Muhammad Ershad; Siregar, Saparuddin; Nurlaila, Nurlaila (Pena Cendekia Insani, 2025)
The increasing complexity of banking operations has increased the risk of fraud, leading to significant financial and reputational losses for financial services institutions (FSIs) in Indonesia. Strengthening internal control systems and implementing comprehensive anti-fraud strategies are crucial, particularly in line with the Financial Services Authority Regulation (POJK) No. 12/2024. This study aims to analyze and develop an anti-fraud strategy model at PT Bank Sumut that is aligned with regulatory provisions and responsive to emerging fraud risks. Using a qualitative descriptive-exploratory approach, data were collected through in-depth interviews with key informants, including anti-fraud unit staff, internal auditors, risk management officers, and compliance officers, complemented by secondary data from policy documents, audit reports, and financial publications. The findings indicate that PT Bank Sumut has implemented anti-fraud strategies based on four pillars: prevention, detection, response, and monitoring-evaluation. Prevention is carried out through stricter Know Your Employee (KYE)/Know Your Customer (KYC) policies, anti-fraud training, and cultivating an integrity-based culture. Detection involves optimizing the whistleblowing system, conducting forensic audits, and using machine learning technology. Response strategies include investigation of SOPs, disciplinary sanctions, and coordination with regulators, while monitoring and evaluation focuses on periodic reviews and benchmarking with best practices. However, challenges remain, particularly in organizational culture and technology adoption. This study proposes an integrated anti-fraud model emphasizing proactive, risk-based, and technology-driven approaches. The model contributes theoretically by expanding the literature on risk management and governance in the banking sector, and practically by offering recommendations for banks and regulators to strengthen fraud prevention mechanisms, enhance public trust, and support financial system stability.